Rough-Cut Capacity Planning By Using the Overall Planning Factors Method: An Applied Study in the Leather Clothes Factory / Textile and Leather Industries Company - Abd Mohammed, Zahra (Opción, 2019)
Most Iraqi industrial companies and factories suffer from a weakness in the capacity planning process because of their lack of reliance on scientific foun- dations in the rough-cut capacity planning process. One of those methods is the overall planning factors method. The research problem focused on ex- plaining how overall Planning factors are used in the rough-cut capacity plan- ning; therefore, the aim of the research is to apply the overall factors in the rough-cut capacity planning through preparing logical steps for the rough-cut capacity planning process by using overall Planning factors. To implement the steps, the mathematical equations have been formulated so that the steps and equations can be used usefully in many industrial companies, and determined the capacity needs for both direct labor time, machine time and for each type of product and the time periods that are specified, as well as determined the capacity needs of each of the work centers. For the purpose of applying the research, the leather garment factory affiliated to the Textile and Leather In- dustries Company was chosen which produces four types of leather garment (men’s jacket, men’s vest, women’s jacket, and women’s coat). The researcher conducted many field visits and interviews to obtain the main data of sched- uling the production as well as historical data related to production quantities and times related to the direct labor and machine and for each type of product. The research concluded that the management of the leather garment factory is not accomplishing the preparation of the master production scheduling accu- rately, and also not using any scientific method in the rough-cut capacity plan- ning. The research also concluded that the process of manufacturing leather garment depends on the direct labor times, which ratio reached to (0.69), while the machine times reached (0.31). Therefore, the research recom- mends for preparing the master production scheduling accurately, as well as relying on the overall Planning factors in the rough-cut capacity plan- ning, and finally the use of the tailor-made machines in the tailor-made center which will help reducing the required time to implement the tai- lor-made process and thus it reduces the manufacturing time.